Amaze: a randomized controlled trial of adjunct surgery for atrial fibrillation. (17th April 2018) - Nashef, Samer A M; Fynn, Simon; Abu-Omar, Yasir; Spyt, Tomasz J; Mills, Christine; Everett, Colin C; Fox-Rushby, Julia; Singh, Jeshika; Dalrymple-Hay, Malcolm; Sudarshan, Catherine; Codispoti, Massimiliano; Braidley, Peter; et al.
Abstract: OBJECTIVES: Atrial fibrillation (AF) reduces survival and quality of life (QoL). It can be treated at the time of major cardiac surgery using ablation procedures ranging from simple pulmonary vein isolation to a full maze procedure. The aim of this study is to evaluate the impact of adjunct AF surgery as currently performed on sinus rhythm (SR) restoration, survival, QoL and cost-effectiveness. METHODS: In a multicentre, Phase III, pragmatic, double-blinded, parallel-armed randomized controlled trial, 352 cardiac surgery patients with >3 months of documented AF were randomized to surgery with or without adjunct maze or similar AF ablation between 2009 and 2014. Primary outcomes were SR restoration at 1 year and quality-adjusted life years at 2 years. Secondary outcomes included SR at 2 years, overall and stroke-free survival, medication, QoL, cost-effectiveness and safety. RESULTS: More ablation patients were in SR at 1 year [odds ratio (OR) 2.06, 95% confidence interval (CI) 1.20–3.54; P  = 0.009]. At 2 years, the OR increased to 3.24 (95% CI 1.76–5.96). Quality-adjusted life years were similar at 2 years (ablation − control −0.025, P  = 0.6319). Significantly fewer ablation patients were anticoagulated from 6 months postoperatively. Stroke rates were 5.7% (ablation) and 9.1% (control) ( P  = 0.3083). There was no significant difference in stroke-free survival [hazard ratio (HR) = 0.99, 95% CI 0.64–1.53; P  = 0.949] nor in serious adverse events, operative or overall survival, cardioversion, pacemaker implantation, New York Heart Association, EQ-5D-3L and SF-36. The mean additional ablation cost per patient was £3533 (95% CI £1321–£5746). Cost-effectiveness was not demonstrated at 2 years. CONCLUSIONS: Adjunct AF surgery is safe and increases SR restoration and costs but not survival or QoL up to 2 years. A continued follow-up will provide information on these outcomes in the longer term. Study registration: ISRCTN82731440 (project number 07/01/34).